1994
DOI: 10.1346/ccmn.1994.0420306
|View full text |Cite
|
Sign up to set email alerts
|

27Al Mas NMR and Aluminum X-Ray Absorption Near Edge Structure Study of Imogolite and Allophanes

Abstract: Abstract--This paper compares the results of 27A1 nuclear magnetic resonance spectroscopy (NMR) and AI-K-edge X-ray Absorption Near Edge Structure (XANES) of natural imogolite and allophanes and some crystaUine reference minerals. All soil allophanes studied contain 4-coordinated A1 (AlIV). The highest relative proportion of A1TM, 21% of the total AI, was found in Si-rich allophane. This value is close to that found in spring allophanes, which were previously considered to be different from soil allophanes. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 45 publications
8
61
1
Order By: Relevance
“…Broad peaks centered at approximately 0.334 nm and 0.222 nm, characteristic of allophane [6,7,27], occur in all samples. Aluminum-rich allophanes (Al 2 O 3 ·xSiO 2 ·yH 2 O (x = 1; y = 2-5)) classified as protoimogolite or imogolite-like allophane [28] can have Al/Si ratios ranging from 2.3 to 2.7 [29], consistent with the observed range of 2.2 to 2.7. The observed XRD reflections are also common to imogolite, although there are additional imogolite reflections [30,31] that are absent in the XRD patterns.…”
Section: Xrd Analysis X-ray Powder Diffraction Patternssupporting
confidence: 77%
See 2 more Smart Citations
“…Broad peaks centered at approximately 0.334 nm and 0.222 nm, characteristic of allophane [6,7,27], occur in all samples. Aluminum-rich allophanes (Al 2 O 3 ·xSiO 2 ·yH 2 O (x = 1; y = 2-5)) classified as protoimogolite or imogolite-like allophane [28] can have Al/Si ratios ranging from 2.3 to 2.7 [29], consistent with the observed range of 2.2 to 2.7. The observed XRD reflections are also common to imogolite, although there are additional imogolite reflections [30,31] that are absent in the XRD patterns.…”
Section: Xrd Analysis X-ray Powder Diffraction Patternssupporting
confidence: 77%
“…Both 29 Si and 27 Al nuclear magnetic resonance spectroscopy (NMR) data were collected for generated solids. • pulse (5 μs) and 180 s relaxation delay at a spinning rate of 10 kHz.…”
Section: Evaluation Of Precipitate Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ildefonse et al (1994) showed that the A1-O bond lengths of imogolite are probably much less diverse than those proposed by Cradwick et al (1972), and therefore it seems likely that the tenmolecular unit cell model should be modified.…”
Section: The Structure Of 1mogolitementioning
confidence: 94%
“…Harsh et al (1992) speculated that imogolite carried a weak structural positive charge. It is clear that such a structural charge cannot involve substitutions such as A1 for Si, because nuclear magnetic resonance (NMR) studies have shown imogolite to consist exclusively of hexavalent A1 and unpolymerized, tetravalent Si (Goodman et al, 1985;Ildefonse et al, 1994). In this paper, I argue that differences in A1-O bond valences can explain why the outer walls of imogolite may develop a weak positive charge that is constant over a wide pH range, whereas the inner walls develop a weak negative charge.…”
Section: Introductionmentioning
confidence: 89%